2012
DOI: 10.1177/0096340212459124
|View full text |Cite
|
Sign up to set email alerts
|

Limits to growth: Can nuclear power supply the world’s needs?

Abstract: Could nuclear power be rapidly expanded on a global scale? There are a number of practical limiting factors, including site availability and acceptability, nuclear waste disposal issues, and the risks of accidents and proliferation. But there are also a variety of resource limitations. One particular resource limitation that has not been clearly articulated in the nuclear debate thus far is the availability of the relatively scarce metals used in the construction of the reactor vessel and core. While this scar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Subtler questions revolved around the best way to meet the demand for electrical energy, now and in the future. Issues of cost, appropriate sites, material degradation during operation of reactors, managing radioactive wastes, accidents, uranium supply, nuclear proliferation, depletion of material resources [18], and the CO 2 emissions of the total nuclear fuel cycle [19] all revealed serious weaknesses of nuclear power.…”
Section: B Ac Kg R O U N Dmentioning
confidence: 99%
“…Subtler questions revolved around the best way to meet the demand for electrical energy, now and in the future. Issues of cost, appropriate sites, material degradation during operation of reactors, managing radioactive wastes, accidents, uranium supply, nuclear proliferation, depletion of material resources [18], and the CO 2 emissions of the total nuclear fuel cycle [19] all revealed serious weaknesses of nuclear power.…”
Section: B Ac Kg R O U N Dmentioning
confidence: 99%
“…In this respect, Derek Abbott suggests that proponents of nuclear power (and those espousing nutopian visions necessarily are) should be subdivided further into 'nuclear realists' and 'nuclear utopians'. 69 'A nuclear realist suggests something on the order of 1 terawatt of nuclear power as part of the global energy mix, providing security in terms of energy diversity and reduced carbon emissions', 70 whereas 'A nuclear utopian', by way of contrast in Abbot's view, 'goes much further and suggests that nuclear power can potentially supply the bulk of the world's energy needs for many thousands of years to come and that perhaps a mix of renewables with nuclear power as the backbone supply is the long-term energy future'. 71 Particularly in the context of ever-increasing energy needs and global climatic change, 'If the utopian vision is a valid one', Abbott argues, 'then it provides considerable impetus to pull together and solve the various practical, safety, and economic problems that currently limit the rapid expansion of nuclear power'.…”
Section: Nuclearism Reconsideredmentioning
confidence: 99%
“…But that too relies on fi nite resources, and several studies have shown that reserves of uranium are already limited and unsustainable (EWG 2006 ;Dittmar 2013 ). The use of fast neutron breeders or perhaps thorium, or even, one day, fusion, might extend the life of the nuclear option, with unknown costs and risks, but not indefi nitely (Abbott 2012 ). We need longerlived energy sources, and we are unlikely to fi nd them in the ground, at least not on this planet.…”
Section: The Changing Energy Contextmentioning
confidence: 99%